A Single-Incision Method for the Removal of Vagus Nerve Stimulators: A Single-Institution Retrospective Review - Michael Baumgartner; Matthew Diehl; James E. Baumgartner (Brain Sciences)
Vagal nerve stimulators (VNSs) improve seizure control in up to half of the patients who have them implanted. In non-responding patients, VNS removal may be necessary. Removal is traditionally accomplished through two incisions. We present our experience removing VNSs through a single incision. Background/Objectives: To determine if VNS removal can be safely performed through a single incision. Methods: The medical records of 73 consecutive patients who underwent VNS removal at our institution from 2012 to 2024 were reviewed. Patients were divided into single-incision and two-incision treatment groups. Operative time and surgical complications were compared between groups. Results: A total of 73 patients underwent VNS removal during the study timeframe. Forty-eight VNS removals were accomplished via a single incision, while 25 required both incisions. Time in the operating room was roughly half as long for single-incision removal vs. two-incision removal (29.4 min, range 11–84 vs. 74.2 min, range 33–203); however, single incision was initially attempted in all cases. In two of the incision cases, the neck dissection resulted in an injury to the internal jugular (IJ) vein. In one case, the IJ was repaired and the lead wire removed. In a second case, the IJ could not be repaired, and a segment of lead wire was retained. In a third case, a short length of lead wire was discovered after a single-incision removal and a second procedure was necessary for removal. There were no significant differences in the rates of transient vocal cord weakness, cough, and/or dysphagia between both treatment groups (p = 0.7368), and there were no cases of permanent nerve palsy. Conclusions: VNS removal can be safely accomplished via a single incision in most cases. Successful single-incision procedures may be shorter than the two-incision approach. Attempted VNS removal via a single incision may result in increased incidence of transient hoarseness, dysphagia, and/or cough, but may result in reduced rates of permanent injury or IJ injury.